A leitura literária e os deficientes visuais : o uso da maquete como recurso tátil - Castro, Sebastião Soares de (2013)
This dissertation approaches the literary reading by visually impaired readers of two cities in Paraná. Therefore, an ethnographic research was developed in two CAPs (Educational Support Center) of the two cities Paranavaí and Maringá, involving 09 students enrolled in elementary and secondary education in public schools. As research tools, questionnaires and oral interviews were used in order to investigate the situation of the participants about their literary preferences as well as the methods and resources exploited for reading achievement. Thus, this research sought to understand this situation considering the social studies of Santos (1989), in understanding the current reality, theorists reception reading with Iser (1996), Jauss (1994), the multimodalities Chartier (1999) and the inclusion of visually impaired readers de Sá, Campos & Silva (2009). It was found, through research, that the selection of literary works varies according to the degree of difficulty of the reader and Braille system domain, coming to the conclusion that literary reading in this procedure does not advance, it is the breaking of horizons of expectation, as Iser (1999) points out. The results show that research participants belong to a pragmatic function of literary literacy, a bit inclusive. In this sense, this work is justified by the formation of visually impaired readers inclusively, aiming their literacy and social inclusion, proposing also to contribute to the improvement of the braile system and other tactile features of literary reading. In this way, use of mock-up as a possible tool for literary reading for the visually impaired is proposed.